The wandering mind: Mental time travel, theory of mind, and language - Corballis,Michael C. (2012)
Mental time travel includes the ability to bring to mind past events (episodic memory) and imagine future ones. Theory of mind is the ability to understand what others are thinking or feeling. Together, these faculties are dependent on the so-called default mode network in the brain, which is active when the mind is not engaged in interaction with the immediate environment. They enable us to mentally escape the present, and wander into past and future and into the minds of others. Language evolved out of gestural systems, probably during the Pleistocene, to enable people to share their mind wanderings, and tell stories, including fictional ones.